2021
DOI: 10.2106/jbjs.20.01226
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic Acid Is Safe in Patients with a History of Coronary Artery Disease Undergoing Total Joint Arthroplasty

Abstract: Background:Tranexamic acid (TXA) is increasingly used to minimize blood loss during total joint arthroplasty (TJA). Although TXA has been shown to be highly effective in reducing operative blood loss, many surgeons believe that it places patients with coronary artery disease (CAD) or a history of coronary stents at an increased risk for myocardial infarction. The purpose of this study was to determine if TXA is safe to use in patients with a history of CAD or coronary stents.Methods:We performed a retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…This analysis is supported by a retrospective chart review of 38,220 TJA patients, where Porter et al, concluded that high-risk patients that receive TXA are not associated with an increase in adverse outcomes. Similar VTE risk profiles have been noted in orthopaedic patients with comorbid CAD and cancer patients undergoing endoprosthetic reconstruction for primary bone sarcoma or metastatic carcinoma to bone 465,466 . The decision to utilize TXA must not be solely based on the theoretical risk of VTE, but instead must weigh all risks and benefits to the medication.…”
Section: - Does Administration Of Tranexamic Acid (Txa) To Patients U...supporting
confidence: 60%
“…This analysis is supported by a retrospective chart review of 38,220 TJA patients, where Porter et al, concluded that high-risk patients that receive TXA are not associated with an increase in adverse outcomes. Similar VTE risk profiles have been noted in orthopaedic patients with comorbid CAD and cancer patients undergoing endoprosthetic reconstruction for primary bone sarcoma or metastatic carcinoma to bone 465,466 . The decision to utilize TXA must not be solely based on the theoretical risk of VTE, but instead must weigh all risks and benefits to the medication.…”
Section: - Does Administration Of Tranexamic Acid (Txa) To Patients U...supporting
confidence: 60%
“…18 In addition, evidence supports there is no increased associated risk of venous thromboembolism (VTE) with TXA usage in orthopedic surgical patients who have known coronary artery disease and/or coronary stents. 19…”
Section: Orthopedic Surgerymentioning
confidence: 99%
“…Recent studies have shown between a 30%–60% reduction in the need for perioperative transfusions with the use of TXA 18 . In addition, evidence supports there is no increased associated risk of venous thromboembolism (VTE) with TXA usage in orthopedic surgical patients who have known coronary artery disease and/or coronary stents 19 …”
Section: Clinical Applications Of Txamentioning
confidence: 99%
“…As for potential risks of the use of TXA, previous studies in patients undergoing total joint arthroplasty have shown that TXA administration is not associated with increased incidence of DVT and PE [29,30].…”
Section: Discussionmentioning
confidence: 99%